The Role of Artificial Intelligence (AI) as a Catalyst for Operational Efficiency Transformation and Product Innovation Disruption in the Startup Ecosystem - Suhartono, Edy; Sulaeman, Moh. Muklis; Suprapto, Hery; Bakri; Muhtarom, Abid (PT. LITERASI SAINS NUSANTARA, 2024)
This study explores the role of Artificial Intelligence (AI) as a catalyst for transforming operational efficiency and disrupting product innovation within the startup ecosystem. Using a qualitative literature review method, data were sourced from 20 rigorously selected scholarly articles out of an initial 40 identified on Google Scholar for the 2004-2024 period. The findings reveal that AI significantly enhances operational efficiency through process automation, data analysis, and accurate market forecasting, as exemplified by Gojek and Halodoc. Additionally, AI facilitates personalized and customer-centric product innovations, as demonstrated by Ruangguru. Despite its clear benefits, challenges such as limited human resources, high implementation costs, and privacy regulations must be addressed. This research underscores the importance of collaboration between startups, the government, and academic institutions to maximize AI's potential in supporting business sustainability and global competitiveness for startups in Indonesia.